LINGUISTIC DISCRIMINATION OF ENGLISH LANGUAGE IN SMAN 2 PINRANG: INFLUENCING OF STUDENTS’ COMPETENCE - Halim, Nelly; Nara, Abdul Wahid (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Linguistic discrimination is critical to student achievement, as it is the intimidating nature of a person's use and style of language that tends to be denigrated or unfairly tolerated in their own environment. The study provide an explanation regarding how discrimination of linguistic can affect student achievement in teaching English at SMA Negeri 2 Pinrang. For the research objective, observations were made in three classes at different times to determine the effect of student achievement. The data were obtained by interviewing two English teachers and six students regarding their views on attitudes and beliefs during the learning process in class. After being analyzed, it appears that there is unconscious discrimination and this can affect the English learning process itself, not respecting the level of the language itself, pressure from the teacher, affecting student competence in some aspects such as fear of communication, homogenization of achievement, fear of evaluation negative, academic, extra visibility of high ability students, mother tongue restriction, difficulty interacting, self-isolation, and discriminatory jokes. The results of this study indicate that all forms of discriminatory behavior both from classmates and teachers can affect student achievement. So that negative behavior also produces negative responses such as fear, anxiety, and separation so that it limits and restrains student participation in the learning process.